Risk stratification after ST-segment elevation myocardial infarction. (1st December 2016) - Buccheri, Sergio; Capranzano, Piera; Condorelli, Antonio; Scalia, Matteo; Tamburino, Corrado; Capodanno, Davide
ABSTRACT: Introduction: Risk stratification according to the timing of assessment, treatment modality and outcome of interest is highly advisable in patients with ST-elevation myocardial infarction (STEMI) to identify optimal treatment strategies, proper length of hospital stay and correct timing of follow-up. Areas covered: This review is an overview summarizing the characteristics and performance of available risk-scoring systems for STEMI. In particular, we sought to highlight the characteristics of STEMI cohorts used for derivation and validation of the available algorithms and appraise their discrimination ability, calibration and global accuracy. Expert commentary: Applying the appropriate score, customized on patients' profile and clinical characteristics at presentation or during the hospitalization, might prove useful to improve the overall quality of care provided to STEMI patients.